Contracting-out at Arbitration II - Verge, Pierre (Relations industrielles / Industrial Relations, 1963)
SummaryThe approach of Quebec arbitrators on the contracting out issue, as expressed in a number of awards rendered before the enactment of section 10 A of the Quebec Labour Relations Act, is examined in order to be compared with American and Canadian Common Law Provinces views.